y = x + 2- - - - - -Equation 1
y = x²- - - - -- - - Equation 2
- - - - - - - -
Insert the y value of equation 2 into equation 1
y = x + 2
x² = x + 2
x² - x = x + 2 - x
x = 2
The answer is x = 2
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
y = x + 2
y = 2 + 2
y = 4
The answer is y = 4
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 1
y = x + 2
4 = 2 + 2
4 = 4
- - - - - - - - - - - -
Check for equation 2
y = x²
4 = (2)²
4 = 4
- - - - - - - - - -
The solution set is { 2, 4}
- - - - - - - - - -s-
2006-12-25 03:08:48
·
answer #1
·
answered by SAMUEL D 7
·
1⤊
2⤋
y=x+2
y=2x ( both x and y should be on one side and nos on other side)
y - x = 2
y - 2x = 0 (multiply with -1) all of them
-----> -y + 2x = 0
y - x = 2 ( cancel the y's)
-------------
x = 2 ( now u found the value of x )
y - x = 2 ( put the value of x )
y - 2 = 2
-----------
y = 2 + 2 = 4 ( now value of y is 4)
to check : ( use anyone of all equations)
y - x = 2
4 - 2 = 2
2 = 2 ( so the values found for x & y is correct)
good luck hope u got the method
mulla sandra u r wrong
2006-12-25 01:26:27
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
This reduces to X^2 = X + 2, for which the solutions are:
X=-1 or X=2. Plug in for the values for Y.
2006-12-24 17:26:36
·
answer #3
·
answered by arbitax 1
·
0⤊
0⤋
y=x^2 or 2x? Either way:
you can substiture in x+2 for y in y=x^2, since y=x+2, so he equation becomes x+2=x^2 or x+2=2x. For the latter equation
2+x-x=2x-x, so
2=x
For x+2=x^2
0=x^2-x-2
so if you plug in the quadratic formula
(1+/- sqrt(1+8))/2=(1+/-3)/2=2 or -1=x
Hope it helps.
2006-12-24 17:29:18
·
answer #4
·
answered by Kevin S 3
·
1⤊
0⤋
Plug it in.
y=4 y=1
OR
x=2 x= -1
2006-12-24 17:37:17
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
x^2 = x +2
x^2 -x -2 = 0
(x-2)(x+1) =0
x-2=0 or x+1 =0
x =2 then y = 4 or
x =-1 then y = 1
2006-12-24 17:47:43
·
answer #6
·
answered by mulla sadra 3
·
0⤊
0⤋
enable 3x -4y = 23 be [a] and 5x +2y = 21 be [b]. Multiply [b] by ability of two on the two factors: 2 * (5x +2y) = 2 * 21 So, 10x +4y = 40 two. enable this be [c]. upload [a] and [c] {3x -4y} + {10x +4y} = 23 + 40 two So, 13x = sixty 5 So, x = 5. placed this fee of x in [a] 3(5) -4y = 23 15 - 4y =23 -4y = 23 -15 -4y = 8 So y = -2 answer set (5, -2)
2016-12-11 15:38:20
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋